Study of breast feeding knowledge among mothers in perinatal period admitted in a tertiary care centre in Dehradun, Uttarakhand, India - Thapliyal, Sunil Kumar; Bangari, Akhil; ., Ruchi (International Journal Of Community Medicine And Public Health, 2019)
Background: Exclusive breast feeding reduces infant and neonatal mortality. NFHS-3 (2005-06) and NFHS-4 (2015-16) (India), showed only marginal improvement from 46% to 55%, regarding exclusive Breast feeding, among children during first 6 months of life. If mother’s knowledge is good, she will be confident to take decision on Breast feeding. This study was conducted to assess, the knowledge, regarding breast feeding, among mothers in perinatal period admitted in a tertiary care centre in Dehradun, Uttarakhand, India. Methods: This was descriptive, cross-sectional study carried out among 300 perinatal mothers. The data was collected using self-administered questionnaires. Results: 95% of mothers knew that the breast milk is best for the baby. 75% of mothers were aware that the breast milk should be the neonates first feed, though only 55% knew about initial breast milk (colostrum). 77% of the mothers said the time for first feed should be within an hour. 27% said baby should be fed as and when hungry. 56% of the mothers stated that the baby should be allowed to feed as long as the baby sucks at the breast. 63.7% mothers were aware about the duration of EBF. Conclusions: Knowledge regarding exclusive breast feeding is inadequate among mothers in Uttarakhand. The government must incorporate breast feeding topic in schools to improve the knowledge on breast feeding, so that mothers can take decision independently.